2021
DOI: 10.1002/cam4.3646
|View full text |Cite
|
Sign up to set email alerts
|

Proton radiotherapy for recurrent or metastatic sarcoma with palliative quad shot

Abstract: Patients with previously treated, recurrent or metastatic sarcomas who have progressed on multiples lines of systemic therapy may have limited options for local control. We evaluated outcomes of palliative proton therapy with the quad shot regimen to unresectable disease for patients with recurrent and/or metastatic sarcoma. From 2014 to 2018, 28 patients with recurrent or metastatic sarcomas were treated to 40 total sites with palliative proton RT with quad shot (14.8 Gy/4 twice daily). Outcomes included toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…Such rapid subjective symptom response after QS1 can be explained by a significant objective response (42.7% of mean GTV reduction) after QS1 ( Fig 2 ). Like the results of quad shot to advanced pelvic or head and neck cancer, 3 , 4 , 5 , 6 , 9 we observed further reduction of residual symptoms and GTVs with additional quad shots (QS2-QS3) to nonosseous metastatic/recurrent sites in our elderly or frail patients. Of the 8 sites that received QS3, all achieved objective radiographic response, including interval stability (RECIST SD, 2 sites) and shrinkage (RECIST PR, 6 sites) after QS1.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Such rapid subjective symptom response after QS1 can be explained by a significant objective response (42.7% of mean GTV reduction) after QS1 ( Fig 2 ). Like the results of quad shot to advanced pelvic or head and neck cancer, 3 , 4 , 5 , 6 , 9 we observed further reduction of residual symptoms and GTVs with additional quad shots (QS2-QS3) to nonosseous metastatic/recurrent sites in our elderly or frail patients. Of the 8 sites that received QS3, all achieved objective radiographic response, including interval stability (RECIST SD, 2 sites) and shrinkage (RECIST PR, 6 sites) after QS1.…”
Section: Discussionsupporting
confidence: 76%
“…Although the number of cases is small and there is heterogeneity in the histology, the responses from quad shots for such low alpha-beta ratio cancers in this case series are comparable to the published data. 9 Lee et al reported results from palliative quad shot using proton beam to 40 recurrent or metastatic sarcomas in various sites (lung, trunk, abdomen, and extremities) showing a 70% subjective palliative response and durable local sarcoma control (11 months of median local progression-free survival). 9 Radiobiologic experiments have suggested that increasing the dose per fraction using hypofractionation may treat those low alpha-beta ratio cancers more effectively than delivering smaller conventionally fractionated doses (1.8∼2.0 Gy/fx).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, several studies on proton therapy show good overall survival and focal control for unresectable malignant soft tissue sarcomas, including leiomyosarcomas. 4 Further exploration of the effectiveness of proton therapy will be possible when more cases are definitively diagnosed using TBCB.…”
Section: Discussionmentioning
confidence: 99%